Adsorptive removal of tetracycline and amoxicillin from aqueous solution by leached carbon black waste and chitosan-carbon composite beads. Issue 1 (February 2021) - Yaqubi, Obaidullah; Tai, Ming Hang; Mitra, Debirupa; Gerente, Claire; Neoh, Koon Gee; Wang, Chi-Hwa; Andres, Yves
Abstract: Carbon black waste as waste by-product of oil refineries, exhibits improved specific surface area and is rich in surface functional groups after leaching. In this work, both powdered leached carbon black waste (LCBW) and LCBW-chitosan composite beads prepared via instantaneous gelation method were utilized as adsorbent to study their adsorption capabilities and behaviors for removal of tetracycline (TC) and amoxicillin (Amox) in distilled and tap water. The characterization showed that LCBW is high in specific surface area ( 375 m 2 /g) and contains carboxyl (‒COOH) and hydroxyl (‒OH) groups which are essential to the adsorption. Under the experimental conditions, adsorption capacities ranging from 12 to 205 mg/g were obtained. It was observed that the adsorption performance of powdered LCBW was enhanced by the cations presented in the tap water while the effect was insignificant to LCBW-chitosan beads. The kinetics studies showed that the adsorption of the studied antibiotics on powdered LCBW and composite beads fitted well with pseudo 1st-order and pseudo 2nd-order model, respectively. The fitting of intraparticle diffusion model showed that the adsorption process was not governed solely by intraparticle diffusion. LCBW-chitosan beads was used to investigate the continuous adsorption of TC in a fixed bed column and the experimental data was fitted to Adams-Bohart model and Thomas model. Graphical Abstract: ga1 Highlights: Leached carbon black waste (LCBW) and LCBW-chitosan composite beads were used for removal of tetracycline and amoxicillin. Adsorption capacities ranging from 12 to 205 mg/g were obtained. Adsorption kinetics of LCBW and LCBW-chitosan composite beads follow pseudo 2nd- order and 1st-order model, respectively. Adsorption of TC on LCBW-chitosan composite beads in a fixed-bed column was studied using Adams-Bohart and Thomas models.